GAMBARAN TINGKAT KECEMASAN PADA ANAK YANG MENGALAMI KEKERASAN DI SEKOLAH DASAR DI KECAMATAN MALALAYANG KOTA MANADO - Lindo, Delarisa R.; Munayang, Herdy; Kaunang, Theresia M.D. (e-CliniC, 2016)
Abstract: Anxiety and other psychiatric disorders such as depression, become as the most suffered mental illness. Each year, an average of 38 million people suffer from anxiety and depression. Anxiety can occur in children when they are facing stressful situations threatening their lives, inter alia violence against children. Children often feel anxious, especially when they lost of love, attention, and support from their parents. This study was aimed to obtain a description of the level of anxiety in children who had experienced violence in elementary school at Malalayang district in Manado. This was a descriptive quantitative study with a cross-sectional design using purposive sampling method. Respondents were fourth grade and sixth grade elementary school children aged 9-12 years. The instrument used was a questionnaire of Revised Children's Manifest Anxiety Scale (RCMAS). The results showed that of 315 children who had experienced violence, there were 246 children (78.09%) had normal anxiety, 41 children (13.02%) had mild anxiety, 21 children (6.67%) had moderate anxiety, and 7 children (2.22%) had severe anxiety. Conclusion: Most of the respondents who experienced anxiety as a result of violence were in the normal anxiety level.Keywords: anxiety, child abuse, children of elementary school age, RCMAS Abstrak: Kecemasan dengan gangguan psikis lainnya yaitu depresi, menjadi penyakit kejiwaan yang paling banyak diderita. Setiap tahunnya rata-rata sebanyak 38 juta orang mengalami kecemasan dan depresi. Kecemasan dapat dialami oleh anak-anak ketika menghadapi situasi stres yang mengancam hidupnya, salah satunya ialah kekerasan pada anak. Anak-anak sering merasa cemas terutama bila kehilangan kasih sayang, perhatian dan dukungan dari orang tuanya. Penelitian ini bertujuan untuk mendapatkan gambaran tingkat kecemasan pada anak yang mengalami kekerasan di Sekolah Dasar (SD) di Kecamatan Malalayang Kota Manado. Jenis penelitian ialah deskriptif-kuantitatif dengan desain potong lintang dan menggunakan purposive sampling. Responden penelitian yaitu anak SD kelas IV-VI usia 9-12 tahun. Instrumen yang digunakan ialah kuesioner Revised Children?s Manifest Anxiety Scale (RCMAS). Hasil penelitian memperlihatkan dari 315 anak yang mengalami kekerasan, terdapat 246 anak (78,09%) mengalami kecemasan normal, 41 anak (13,02%) mengalami kecemasan ringan, 21 anak (6,67%) mengalami kecemasan sedang, dan 7 anak (2,22%) mengalami kecemasan berat. Simpulan: Sebagian besar responden yang mengalami kecemasan akibat kekerasan berada dalam kondisi kecemasan normal. Kata kunci: kecemasan, kekerasan pada anak, anak usia sekolah dasar, RCMAS